The Influence of Entrepreneurial Knowledge, Entrepreneurial Motivation, and Commitment on Entrepreneurial Intentions of Makassar State University Students - Arisah, Nur; Putrawan, Muh. Rizah (International Journal of Education, Vocational and Social Science, 2025)
The research was conducted with the aim of knowing whether there is an influence between entrepreneurial knowledge, entrepreneurial motivation, and commitment to student entrepreneurial intentions, especially in the Economics Education Study Program, Faculty of Economics and Business, Makassar State University. This research uses a quantitative approach with multiple regression data analysis techniques. Data collection techniques through questionnaires and literature study. The results showed that (1) the entrepreneurial knowledge variable had a positive and significant effect on students' entrepreneurial intentions; (2) the variable of entrepreneurial motivation has a positive and significant influence on students' entrepreneurial intentions; (3) the commitment variable also has a positive and significant influence on students' entrepreneurial intentions; (4) entrepreneurial knowledge, entrepreneurial motivation, and commitment have a simultaneous influence on students' entrepreneurial intentions in the Economics Education study program, Faculty of Economics and Business, Makassar State University. In addition, it is known that the entrepreneurial intention factor (Y) of students is 64.7% influenced by entrepreneurial knowledge (X1), entrepreneurial motivation (X2), and commitment (X3). The remaining 35.3% is influenced by other variables outside of the research conducted, such as: family factors, environment, personal values, gender and age.